Archaeological perspectives on the Southern Appalachians : a multiscalar approach - Meyers, Maureen S.; Gougeon, Ramie A. (University of Tennessee Press, 2015)
"This volume demonstrates how archaeologists working in the Southern Appalachian region over the past 40 years have developed rich interpretations of prehistoric and historic Southeastern Native societies by examining them from multiple scales of analysis. The end results of these examinations demonstrate both the uses and the constraints of multiscalar approaches in reconstructing various lifeways across the Southeast"--